In-silico and in-vitro analysis of novel substituted benzimidazolyl derivatives for antimycobacterial potentials targeting enoyl acyl carrier protein reductase (InhA) - Umaa Kuppuswamy; Ravi Kumar Rajan; Arvinth Kumar; Muthiah Ramanathan (SpringerOpen, 2022)
Abstract Background The emergence of mutated drug-resistant strains of Mycobacterium tuberculosis has reinvigorated the development of effective chemotherapy for MDR-TB (multidrug-resistant resistance tuberculosis). Enoyl acyl carrier protein reductase (InhA) involved in the mycobacterial fatty acid elongation system has been chosen as a potential target. Result All of the lead compounds had a definite Rf value and a sharp melting point, confirming that no tautomeric forms exist and that the keto (CO) group is apparent in the IR and 13C NMR spectrum data. Structure-based drug design revealed the presence of amino acid residues like TYR 158, ILE 194, and PHE 149 which are crucial for InhA inhibitory activity and were considered favorable interactions. Among all, compounds 4, 5a, and 5c showed better docking and binding free energy owing to favorable interactions. Interestingly, there was a strong correlation between the binding free energy and the antimycobacterial susceptibility assay, where compounds 4, 5a, and 5c had greater activity. All the lead compounds also had good oral absorption and gut permeability. The presence of a carboxylic linker (-COOH-) between benzimidazole and the rest of the structure of the lead compounds was found to be crucial for activity as the oxygen atom and hydroxyl group of the linker formed most of the favorable interactions. The presence of chlorophenyl showed a favorable effect on InhA inhibition which might be owing to its hydrophobic interaction with PHE 149. Conclusion Three of the seven lead compounds synthesized had an IC value of approximately 0.5 μg/ml in the in-vitro Alamar blue assay against the Mycobacterium tuberculosis H37Rv strain, which is roughly comparable to the standard marketed drug, Isoniazid (INH). This manifestation of promising activity that resulted from combining in-silico and wet lab experimentation could be a great starting point for developing potent antimycobacterial agents to combat multidrug-resistant tuberculosis. Graphical abstract